Evaluation of the progesterone receptor status in breast cancer using three different antibodies: a comparison by Allred score system - Daltoé, Renata Dalmaschio (e-Century Publishing Corporation, 2013)
Breast cancer (BC) hormonal receptors status is assessed by immunohistochemistry (IHC), a specific, sensitive, and accessible method that guide breast cancer treatment. In this study, we evaluated progesterone receptor (PR) expression in 53 BC cases using 3 anti-PgR antibodies (AB): monoclonal (SP42 and PgR636) and polyclonal ab62621. Primary BC cases (with signed informed consent) were used to generate tissue microarray platforms, where PR expression was accessed by IHC and evaluated by the Allred score. Categorical and quantitative data are shown in percentage and mean, respectively. Concordance (CON) and correlation among ABs were analyzed by Kappa factor (Κ), Spearman’s correlation coefficient (ρ) or intraclass correlation coefficient. Staining patterns of each AB were compared by paired T-Test. We noted poor CON and Κ between ab62621 vs SP42 (CON=64.1%; Κ=0.247), and ab62621 vs PgR636 (CON=62.3%; Κ=0.204), but higher CON between SP42 vs PgR636 (CON 90.6%; Κ=0.738). Data were corroborated by Mc Nemar statistical test (p=0.019, p=0.014 and p>0.05, respectively). Regarding staining intensity (SI) among PgR+ samples, we found higher proportion of weak staining and lower SI for ab62621 (48.3%; mean IS=1.6), when compared to SP42 (20.0%, mean IS=2.1, T-test p<0.01) and PgR636 (2.3, 21.9%, T-test p<0.01). Within the entire sample, similar results were observed following ρ: SP42 vs PgR636 (ρ=0.8103); ab62621 vs SP42 (ρ=0.3524); ab62621 vs PgR636 (ρ=0.4075). As for proportion of stained cells and proportion score (PS), among PgR+ samples, the mean values for ab62621 (75.4%; 4.8) were significantly higher than those of SP42 (56.3%, 4.3; T-test p<0.01) and RPG636 (60.1%; 4.2; T-test p<0.01). Similar data were found after analyzing PS for the entire sample: SP42 vs PgR636 (ρ=0.8588); SP42 vs ab62621 (ρ=0.4832); RPG636 vs ab62621 (ρ=0.4050). Our data indicate that anti-PgR monoclonal ABs, PgR636 and SP42, are, unlike ab62621, equally suitable to test BC PgR status by IHC due to their higher accuracy. Therefore, we suggest their clinical use during BC diagnosis; thus, enabling more precise therapeutic decisions to treat BC.